The Impact of Skiing on the Visual System: Injuries, Dysfunctions and Ways of Prevention - Dominik Rabstein; Piotr Gosciniewicz; Adam Kabiesz; Radosław Szydłowski; Agnieszka Porwolik; Magdalena Bodera; Hanna Porwolik; Agata Porwolik (Journal of Education, Health and Sport)
Skiing, although it offers numerous health and emotional benefits, is associated with the risk of eye injuries. In high-altitude conditions, the eyes are exposed to intense UV radiation reflected by the snow, which can lead to snow blindness (photokeratitis). This condition manifests itself with severe pain, photophobia, and tearing, and its more serious consequences can include permanent corneal opacities. Additionally, extreme weather conditions, such as strong wind and low temperatures, favor drying of the eye surface and irritation of the conjunctiva.